Dog Code: Human to Quadruped Embodiment using Shared Codebooks - Mc Donnell, Rachel (My University, 2024)
Many VR animal embodiment sytsems suffer from poor animation fidelity, typically animating the animal avatars using inverse kinematics. We address this issue, presenting a novel deep-learning method, centred around a shared codebook, for mapping human motion to quadruped motion. Rather than trying to directly bridge the gap from human motion to quadruped motion, a task which has proven difficult, we first use a rule-based retargeter, relying on inverse and forward kinematics, to retarget human motions to an intermediate motion domain in which the motions share the same skeleton as the quadruped. We then use finite scalar quantization to construct a shared latent space, or codebook, between this intermediate domain and the quadruped motion domain. We do this by first pre-defining a finite number of discrete latent codes and then teaching these codes, using unsupervised deep-learning, to represent semantically similar motions in the two domains. We in- corporate our real-time human-to-quadruped motion mapping into a VR quadruped embodiment system. The output quadruped animations are natural and realistic, while also preserving the semantics of users’ actions. Moreover, there is a strong synchrony between the input human motions and retargeted quadruped motions, an important factor for inducing a strong sense of VR embodiment.
Proceedings of the 17th ACM SIGGRAPH Conference on Motion, Interaction, and Games
PUBLISHED
USA
Keywords: VR embodiment, Quadruped embodiment, Motion retargeting, Deep- learning; Creative Technologies